Exploring how teachers construct their professional identity through a grounded theory approach: Insights from a systematic literature review - Benny Dele Bintang Ananta; Rey Ardella Rahmadhany; Andi Nur Hafidzah Alfiyah Qashas; Adinna Silky Nuriyah; Siti Muniroh (Universitas Muhammadiyah Malang, 2026)
This study explores the development of teacher professional identity (TPI) by integrating a 2020 PRISMA-based Systematic Literature Review (SLR) with Straussian Grounded Theory (GT) analysis to produce a multilevel conceptual model. Using a qualitative integrating with systematic review design, studies were identified, screened, and analyzed following PRISMA procedures, and subsequently coded through open, axial, and selective coding based on the Straussian GT approach. The SLR identified fifteen robust GT studies from ten countries, demonstrating a clear increase in TPI research using GT, especially after 2020. The Straussian GT tradition dominated (60.0%), and manual coding (53%) was the most common analysis technique, followed by NVivo and MAXQDA. The studies included diverse samples, ranging from four to over two hundred participants. ​The GT analysis conceptualized Teacher Professional Identity Formation as the central phenomenon. This process was shaped by a coding process that included 673 items and then categorized into sixty-four subcategories, and by causal factors (personal history, motivation, and policies), contextual factors (institutional and cultural norms), and influencing factors (mentorship and emotions). Teachers adopted action strategies such as adaptive coping and reflective practice to manage identity tensions. The consequences include both positive (practice excellence, autonomy, and inclusiveness) and negative (burnout and identity destabilization) outcomes. The resulting model provides an integrated framework that explains the negotiation of TPI in an evolving sociocultural environment.